2017 16th International Superconductive Electronics Conference (ISEC) 2017
DOI: 10.1109/isec.2017.8314196
|View full text |Cite
|
Sign up to set email alerts
|

Traveling-Wave Parametric Amplifier Based on Three-Wave Mixing in a Josephson Metamaterial

Abstract: We have developed a recently proposed concept of a Josephson traveling-wave parametric amplifier with threewave mixing. The amplifier consists of a microwave transmission line formed by an array of nonhysteretic one-junction SQUIDs. These SQUIDs are flux-biased in a way that the phase drops across the Josephson junctions are equal to 90°. Such a onedimensional metamaterial possesses a large quadratic nonlinearity and zero cubic (Kerr-like) nonlinearity. This property allows phase matching and exponential power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 12 publications
0
40
0
Order By: Relevance
“…A good understanding of the nonlinear behavior of this Josephson photonic crystal opens door to further more fundamental experiments with such devices. Finally, we demonstrated the possibility to implement TWPA made from SQUID, which could lead in the future to third-order Kerr nonlinearity TWPA, based on the SNAIL geometry [17,[55][56][57] or to TWPA with vanishingly small fourth-order Kerr nonlinearity [58,59]. Methods Theoretical model.…”
Section: Resultsmentioning
confidence: 99%
“…A good understanding of the nonlinear behavior of this Josephson photonic crystal opens door to further more fundamental experiments with such devices. Finally, we demonstrated the possibility to implement TWPA made from SQUID, which could lead in the future to third-order Kerr nonlinearity TWPA, based on the SNAIL geometry [17,[55][56][57] or to TWPA with vanishingly small fourth-order Kerr nonlinearity [58,59]. Methods Theoretical model.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that feeding the amplifier with bimodal Fock input states leads to a quantification for the noise estimators that is within the SQLs, while when exploiting bimodal coherent input states these limits can be exceeded. The results represent a key model to predict the behaviour of rf-SQUID based JTWPA [18], [19] and other Josephson-based metamaterials [23] for quantum computing (via quantum limited amplification of complex signals) [17], [26], [27] and for quantum information (via the generation of non-classical radiation [5]- [8], [28]) in non-ideal cryogenic environment [29].…”
Section: Discussionmentioning
confidence: 95%
“…These devices could be used as Josephson Traveling Wave Parametric Amplifiers, based on four-wave mixing [10,11,22]. Their fluxtunability offers interesting perspectives regarding threewave mixing [34,35] or Kerr-free [36,37] J-TWPA. These devices could also be used to perform new quantum optics experiments in the microwave domain [38].…”
Section: Discussionmentioning
confidence: 99%